Some like it hot: Is the recent presence of the meadow-forming Penicillus capitatus in the Azores connected to global warming? - Gabriel, Daniela (2024)
Specimens found in a tide pool on Santa Maria Island (Azores) were identified in situ as the green alga Penicillus capitatus (Halimedaceae, Bryopsidales). DNA-based analyses of two genetic markers (rbcL and tufA) confirmed the identification and indicated that the Azorean population is closely related to those from the Western Atlantic. P. capitatus is newly reported for the Azores, with the nearest population in the Madeiran archipelago since 1978. The present record expands the species distribution further north outside the Mediterranean basin. Simulation of particle dispersal indicates that the species could reach the Azores within a year from any place in the North Atlantic where it is known to occur. Therefore, P. capitatus most likely arrived by rafting through marine cur rents, though anthropogenic introduction has not been excluded. While its natural arrival in the Azores may have occurred multiple times, its current successful establishment is likely related to the recent warmer conditions of the Azorean waters, estimated to have increased by 1.05º C over the last four decades. Prospection on sandy bottoms should be performed to assess the distribution of the species in the archipelago. DNA sequence analyses, including representatives of other P. capitatus populations, are necessary to enable further studies at a phylo geographical level.